Plesiomonas shigelloides: Um enteropatógeno emergente? - Falcão, Juliana Pfrimer; Gibotti, A. A.; Souza, R. A.; Campioni, F.; Falcão, D. P. [UNESP] (My University, 2007)
Plesiomonas shigelloides is a Gram-negative rod-shaped bacterium, of the family Enterobacteriaceae, which has been isolated from freshwater and salt water, freshwater fish, shellfish and many species of animals. Most human P. shigelloides infections are suspected to be waterborne. The organism can be found in untreated water used as drinking water, in recreational water, or in water used to rinse food that is consumed without cooking or heating. The ingestion of P. shigelloides does not always cause illness in the host animal, and the organism may be present temporarily as a transient, noninfectious member of the intestinal flora. It has been isolated from the stools of patients with diarrhea,but it is also sometimes isolated from healthy individuals. P. shigelloides has been implicated in gastroenteritis, usually a self-limiting disease characterized by fever, chills, abdominal pain, nausea, diarrhea or vomiting; in severe cases the diarrhea may be yellowish-green, foamy and tinged with blood. The bacteria may also cause extra-intestinal infection. Furthermore, it can produce toxins and may be invasive. The evidence in favor of considering P. shigelloides as an enteropathogen is not totally convincing. Although it has been isolated from patients with diarrhea and incriminated in some outbreaks involving contaminated water and food, it was not possible, in many P. shigelloides samples associated with gastrointestinal infections, to identify a definite mechanism of virulence.

Plesiomonas shigelloides é um bacilo Gram-negativo, pertencente à família Enterobacteriaceae, isolado de água doce e salgada, de peixes de água doce, mariscos e de inúmeros tipos de animais. Suspeita-se que a maioria das infecções humanas causadas por P. shigelloides, seja veiculada pela água, pois a bactéria está presente em águas não tratadas que são usadas para beber, águas recreacionais ou água para lavar alimentos que são consumidos sem cozimento ou aquecimento. A ingestão de P. shigelloides não causa sempre doença no animal hospedeiro, mas o microrganismo pode permanecer temporariamente como membro transitório não infeccioso da microbiota intestinal. A bactéria é isolada de fezes de pacientes com diarréia, mas algumas vezes também de fezes de indivíduos sem sintomas. A doença causada por P. shigelloides é a gastrenterite, que normalmente é auto-limitante, com febre, calafrio, dor abdominal, náusea, diarréia ou vômito. Em casos graves, as fezes diarréicas podem ser verde-amareladas, espumosas e com presença de sangue. A bactéria pode também causar infecções extra-intestinais. Ademais, pode produzir toxinas e ser invasora. As características utilizadas para considerar P. shigelloides como um enteropatógeno não são totalmente convincentes. Embora seja isolada de pacientes com diarréia e incriminada em vários surtos epidêmicos envolvendo água e alimentos contaminados, não foi possível identificar em muitas amostras de P. shigelloides, associadas com infecções gastrintestinais, um mecanismo de virulência definitivo. Palavras-chave: P. shigelloides; enteropatógeno; gastrenterite; diarréia; infecções extra-intestinais.
Plesiomonas shigelloides: An emergent enteropathogen?
Keywords: Diarrhea; Enteropathogen; Extraintestinal infections; Gastroenteritis; P. shigelloides; cardiotoxin; cotrimoxazole; drinking water; elastin; enterotoxin; fresh water; hemagglutinin; hemolysin; histamine; tetrodotoxin; toxin; abdominal pain; antibiotic sensitivity; bacterial virulence; bacterium isolation; cardiotoxicity; chill; cooking; diarrhea; disease association; disease severity; Enterobacteriaceae; enteropathy; epidemic; feces; fever; fish; food contamination; gastroenteritis; Gram negative bacterium; heating; host; human; ingestion; intestine flora; intestine infection; nonhuman; Plesiomonas shigelloides; review; shellfish; shigellosis; vomiting; water contamination